Ang Tungkulin ng kritisismo sa Filipinas - Almario, Virgilio S. (Quezon City Ateneo de Manila University Press, 2014)
History and criticism on Philippine literature.
Includes bibliographical references (page 324) and index.
In Filipino.
Keywords: Philippine literature -- History and criticism. -- 19th century; Philippine literature -- History and criticism. -- 20th century